Thecoma in an Elderly Crioulo Mare - Santos, Fernanda Carlini Cunha; Aquino Franco, Fernanda; Piazza, Thaisi; Zanella, Ricardo; Bondan, Carlos; Porto Alves, Leonardo (Acta Scientiae Veterinariae, 2023)
Background: Ovarian enlargement in mares can either be a physiological or pathological condition associated with neoplastic or non-neoplastic causes. Neoplasia is more prominent in elderly than young horses. Granulosa cell tumors are the most common neoplastic cause of ovarian enlargement, while thecoma is the rarest. Thecoma is a benign ovarian stromal neoplasia originating from the sexual cords of the embryonic gonad and can affect the production of steroid hormones, leading to changes in behavior and the estrous cycle. If only one ovary is affected, after unilateral ovariectomy, usually the mare can still be used for reproductive purposes, after unilateral ovariectomy. Herein, we report a case of ovarian thecoma in an elderly Crioulo mare. Case: A 15-year-old Crioulo mare was evaluated for progressive weight loss. The mare presented a low body score, and on physical examination, all parameters were within reference limits. Hematological examination revealed anemia, hyperfibrinogenemia, and neutrophilia. Serum biochemistry examination were within the physiological limits. Rectal palpation revealed an increase in volume in the left ovary (4.3 × 2.9 × 3 cm), smooth consistency and no associated pain in either of the ovaries. Rectal ultrasonography revealed a heterogeneous pattern, suggesting a neoplasm. As a treatment modality and for definitive diagnosis, the mare underwent a unilateral flank ovariectomy laparoscopically in the quadrupedal position. On histopathological evaluation of the ovaries, the sample showed cysts associated with proliferating spindle cells arranged in a solid arrangement, occasionally forming eddies, in addition to hemosiderosis, with clear cytoplasm and lipid vacuoles. Macroscopically, the ovary presented with a regular surface, smooth to firm consistency, a homogeneous brownish appearance with blackened foci, and brownish fluid-filled cysts. These findings confirmed thecoma of the left ovary in the mare. Discussion: Ovarian enlargement in mares may be physiological or an indication of pathological conditions, associated with both non-neoplastic and neoplastic etiology. Clinical signs of ovarian neoplasms can be nonspecific; therefore, to arrive at a definitive diagnosis, it is imperative to evaluate and compare the patient's history, physical examination, and results of complementary examinations. Excessive production of hormones lead to behavioral changes in mares with ovarian tumors, such as masculinized or aggressive behavior, and anestrus persistence. Thecomas may or may not interfere with steroid production and levels. On ultrasound examination, ovarian neoplasms may present similar echogenicity patterns. Histopathological evaluation is the best diagnostic approach after an ovariectomy. The prognosis of ovariectomy is considerably successful with the mare regaining reproductive health, although some mares may become infertile, with a small, inactive contralateral ovary. Thecoma is a rare neoplasm in horses; however, owing to its potential to cause altered reproductive functions, it should be considered as a differential diagnosis in mares with increased ovarian volume. Keywords: theca cell, histopatology, neoplasia, ovary.